The Jewish Temple: a non-biblical sourcebook - Hayward, Robert (Routledge, 1996)
"This book uncovers the meaning and significance of the Jewish Temple and its Service during the last centuries of its existence. The non-biblical sources indicate that the Temple and its rites were seen as holding the universe together, providing order and meaning in a world which would overwise easily lapse into chaos."--Jacket